Challenging Political Representation in the Era of Big Data - Eidikytė, Kristina (Politologija, 2024)
This article deals with the problem of the change in the theoretical conception and practical realisation of political representation in the era of big data, i.e. in the 20th and 21st century, when IT data processes have become an almost integral part of the political life of citizens. Based on the concepts of the philosophers F. Ankersmit and J. Baudrillard, the article analyses why, despite the arguments of critical data studies, the forms of political representation affected by big data are still considered objective. After presenting research on the characteristics of political representation in the information technology-dominated public sphere and smart cities, the article identifies signs of the decline of contemporary political representation: the compression of public space and the legitimation processes of datafication facilitated by big data in the smart city. The continuation of the article’s theme and the analysis of the problems are recommended to be pursued in the field of post-political discussions.
Keywords: Political representation; datafication; public space; smart city; post-politics; big data; challenges